PENGARUH SPPT, PENGETAHUAN DAN KESADARAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI DESA RIARAJA KECAMATAN ENDE - Bedhu, Maria Risna Anggo Ri; Kapa, Sesilianus (Program Studi Akuntansi Universitas Flores, 2022)
The purpose of this study was to determine the effect of SPPT, knowledge and awareness of taxpayer compliance in paying land and building taxes. This type of research is quantitative. The population in this study is land and building tax payers who are registered at the Riaraja Village Office, Ende District until 2022 totaling 127. The sample technique uses purposive sampling. The number of samples in this study were 56 taxpayers. This study uses primary data, namely a questionnaire. Data were analyzed using multiple regression analysis which was processed through IMB SPSS Statistics ver 24. The results of this study indicate that: (1) SPPT has an effect on compliance with paying land and building taxes. The test results show that the variable coefficient value of tax returns is 0.190 with tcount > ttable (2.296 > 2.00665) and a significant level of 0.026 <0.05. (2) Knowledge of taxpayers influences compliance with paying land and building taxes. The test results show a variable coefficient value of 0.161 with tcount > ttable (2.296 > 2.00665) and a significant level of 0.035 <0.05. (3) Taxpayer awareness influences compliance in paying land and building taxes. The test results show a variable coefficient value of 0.342 with tcount > ttable (3.229 > 2.00665) and a significant level of 0.002 <0.05. Simultaneously or simultaneously, the variables of tax returns payable, taxpayer knowledge and taxpayer awareness have a significant effect on compliance with paying land and building taxes by 37.6%. While the remaining 62.4% is influenced by other variables not included in the study.